2016
DOI: 10.1038/pr.2016.128
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and phenotypic characteristics of 293 Danish girls with tall stature: effects of oral administration of natural 17β-estradiol

Abstract: Serum IGF-I was elevated tall statured children, but did not predict the effect of treatment with 17β-estradiol, which caused a modest reduction in final adult height.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
(52 reference statements)
1
6
2
Order By: Relevance
“…Thus, NGS studies seem to provide additional diagnostic yield particularly in those tall subjects with additional clinical features. Conversely, in our cohort and those of previous retrospective studies, karyotyping appears to be much less useful [8,9]. In fact, in our study karyotype was normal in over 96% of the subjects.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Thus, NGS studies seem to provide additional diagnostic yield particularly in those tall subjects with additional clinical features. Conversely, in our cohort and those of previous retrospective studies, karyotyping appears to be much less useful [8,9]. In fact, in our study karyotype was normal in over 96% of the subjects.…”
Section: Discussioncontrasting
confidence: 93%
“…The aetiology of tall stature has previously been described in only five notable cohort studies with diverse inclusion criteria and varying reported rates of detected pathology [8] , [9] , [10] , [11] , [12] . However, the few previous studies have been affected by apparent selection bias [8] , [9] , [10] , [11] , [12] , and importantly, included a minimal number of extremely tall subjects [ [8] , [9] , [10] , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The moderate height reduction, risk of impaired fertility in women and melanomas argue against routine use of high-dose sex steroids in adolescents with idiopathic tall stature (62,63,64). In the exceptions where treatment is initiated, high-dose ethinyl estradiol or natural estradiol is used to ensure an early and rapidly progressing puberty (65). Tall statured boys have been given very high testosterone doses (testosterone enanthate 250-500 mg every 2 weeks (66)) with significant reduction in final height if treatment is initiated early.…”
Section: Treatment With Exogenous Administration Of High-dose Sex Stementioning
confidence: 99%
“…In the last years, it has been considered a surgical closure of the epiphyses, a great option especially in patients whose bone age is 12 years or above, when any medical intervention is unlikely to produce significant reductions in adult height [72]. Upners et al showed a 1.6 cm reduction in 18 of 26 girls treated with physiological doses of 17β-estradiol at the bone age above 12 years [65]. The most common surgical procedure for reducing growth is bilateral percutaneous epiphysiodesis of the distal femur and proximal tibia and fibula.…”
Section: Treatment Of Tall Staturementioning
confidence: 99%